1986
DOI: 10.1210/endo-119-6-2484
|View full text |Cite
|
Sign up to set email alerts
|

Direct Effect of Estradiol on the Number of Dopamine Receptors in the Anterior Pituitary of Ovariectomized Rats

Abstract: The effect of 17 beta-estradiol (17 beta E2) on anterior pituitary dopaminergic receptor (D2) content was studied in vitro in relation to PRL secretion. Anterior pituitaries from ovariectomized rats were incubated for short periods in medium 199, with or without the steroid. Dopamine (DA) receptors in partially purified pituitary membranes were quantified by equilibrium binding using [3H]spiperone; the PRL released into the incubation medium was analyzed by RIA. Addition of 10(-10) to 10(-6) M 17 beta E2 to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 18 publications
3
19
0
Order By: Relevance
“…Although it is well known that dopamine plays a major role in the control of prolactin release [4,11], prolactin synthesis and secretion are also regulated by several hypothalamic hormones. Thyrotropin-releasing hormone (TRH) is a primary secretagogue [12].…”
Section: Department Of Obstetrics and Gynecology Shimane University mentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is well known that dopamine plays a major role in the control of prolactin release [4,11], prolactin synthesis and secretion are also regulated by several hypothalamic hormones. Thyrotropin-releasing hormone (TRH) is a primary secretagogue [12].…”
Section: Department Of Obstetrics and Gynecology Shimane University mentioning
confidence: 99%
“…It has been reported that there is marked hyperplasia of lactotrophs during pregnancy and lactation in humans [2]. Exogenous E2 is known to induce lactotroph hyperplasia [3], and increases prolactin release from rat pituitary cultures by desensitizating lactotrophs to dopamine, a well-known inhibitor of prolactin release [4]. E2 was also reported Effects of estradiol and progesterone on prolactin transcriptional activity in somatolactotrophic cells Tselmeg Mijiddorj, Haruhiko Kanasaki, Indri Purwana, Sukhbaatar Unurjargal, Aki Oride and Kohji Miyazaki…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…17&Estradiol (E,) stimulates PRL secretion by a direct action on pituitary cells in which it both enhances PRL mRNA production dramatically and increases the mitotic activity of PRL cells (Lieberman et al, 1982;Takahashi and Kawashima, 1987). Moreover, in vitro studies suggest that the direct effect of E, on PRL cells could be exerted by two other mechanisms: an increase in their sensitivity to thyrotropin-releasing hormone (TRH), one of the most potent PRL-releasing factors (PRF), and a decrease in their sensitivity to dopamine, considered as the most likely PRL-inhibiting factor (De Lean et al, 1977;Pasqualini et al, 1986;Zhang et al, 1990). Further in vivo studies also indicate that estrogens not only act directly on the lactotrophs but also modulate activity of the central system which controls PRL pituitary release (Fink, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, estrogens exert demonstrable effects on rat PRL synthesis and gene transcrip tion [4,7]. Pasqualini et al [8] reported that 17 |)-estradiol (E2) had a direct effect on the number of dopamine receptors in the anterior pituitary of ovariectomized rats, and suggested that the stimulatory effect of estradiol on PRL secretion may be due to the desensitization of these cells to dopamine. The effect estra diol exerts on PRL release can be shown using long-term cultures of dispersed anterior pituitary cells with a suitable Received: October 3, 1988 Accepted after revision : February 23, 1989 preincubation time, but it is rare to duplicate this effect using short-term cultures.…”
mentioning
confidence: 99%